2022
DOI: 10.1001/jamanetworkopen.2022.33080
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Asian American Populations in Medical School Curricula

Abstract: ImportanceDespite being one of the fastest-growing populations in the US, the Asian American population is often misrepresented in and omitted from health research and policy debate. There is a current lack of understanding of how Asian American populations are portrayed in medical school curricula.ObjectiveTo assess how Asian American populations and their subgroups are represented in medical school curricula.Design, Setting, and ParticipantsIn this qualitative study, the content of 632 lectures from all 19 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Participants also described the absence of and desire for including Asian American health issues within the medical curriculum. This finding is consistent with previous work that found that Asian Americans were omitted and needed more dedicated time in the curriculum 52 , 53 and expands prior studies by specifically calling for this teaching within the medical curriculum. 10 These findings warrant the introduction of Asian American health and history lectures within the medical school curriculum.…”
Section: Discussionsupporting
confidence: 91%
“…Participants also described the absence of and desire for including Asian American health issues within the medical curriculum. This finding is consistent with previous work that found that Asian Americans were omitted and needed more dedicated time in the curriculum 52 , 53 and expands prior studies by specifically calling for this teaching within the medical curriculum. 10 These findings warrant the introduction of Asian American health and history lectures within the medical school curriculum.…”
Section: Discussionsupporting
confidence: 91%